Total tanshinones ameliorates cGAS-STING-mediated inflammatory and autoimmune diseases by affecting STING-IRF3 binding - Chengwei Li; Jincai Wen; Xiaoyan Zhan; Wei Shi; Xiu Ye; Qing Yao; Simin Chen; Congyang Zheng; Xianlin Wang; Xinru Wen; Xiaohe Xiao; Yinghao Wang; et al. (Chinese Medicine, 2024)
Abstract Background An important signaling pathway connecting illness and natural immunity is the cyclic GMP-AMP synthase (cGAS)-stimulator of interferon genes (STING) pathway, but aberrant activation of this pathway is associated with the development of autoimmune and inflammatory diseases. Hence, targeted inhibition of the activation of the cGAS-STING pathway is potentially valuable in the treatment of disease. The primary active component of Salvia miltiorrhiza is total tanshinone (TTN). Research has indicated that TTN possesses noteworthy anti-inflammatory properties. However, the protective mechanism of TTN against acute liver injury (ALI) and autoimmune diseases is unknown. Methods A model of aberrant activation of the cGAS-STING pathway was established in various cells and treated with TTN, and the expression of cGAS-STING pathway-related proteins, type I interferon, interferon stimulated genes and inflammatory factors was assessed by western blotting, real-time qPCR. Immunofluorescence analysis of the effect of TTN on the entry of associated proteins into the nucleus following aberrant activation of the cGAS-STING pathway. The effect of TTN on STING oligomerisation was investigated using 2'-3'-cyclic GMP-AMP (2',3'-cGAMP) to induce STING oligomerisation. Western blotting was used to examine the impact of TTN on the interactions of STING, tank-binding kinase 1 (TBK1), and interferon regulatory factor 3 (IRF3) after HA or Flag-labelled plasmids were transfected into HEK-293 T cells. A dimethylxanthenone-4-acetic acid (DMXAA) -induced activation model of the cGAS-STING pathway in mice was established to study the effect of TTN on aberrant activation of the cGAS-STING pathway in vivo. On the other hand, an animal model of lipopolysaccharide/D-galactosamine (LPS/D-GaIN)-induced ALI and an autoimmune disease model induced by trex1 knockout were established to study the effects of TTN on inflammatory and autoimmune diseases mediated by the cGAS-STING pathway in vivo. Results In several models of aberrant activation of the cGAS-STING pathway, TTN significantly inhibited the phosphorylation of STING and IRF3, thereby suppressing the expression of type I interferon, interferon-stimulated genes and inflammatory factors. Additionally, TTN prevented P65 and IRF3 from entering the nucleus after the cGAS-STING signalling pathway was abnormally activated. Subsequent research indicated that TTN was not involved in the oligomerization of STING or the integration of STING-TBK1 and TBK1-IRF3. However, TTN was found to have a substantial effect on the binding process between STING and IRF3. On the other hand, DMXAA-induced STING activation and activation of downstream signalling in vivo are inhibited by TTN. Furthermore, TTN exhibits positive treatment effects on autoimmune diseases caused by deficiency of trex1 and LPS/D-GaIN-induced ALI. Conclusion Our research indicates that TTN effectively treats ALI and autoimmune illnesses mediated by the cGAS-STING pathway by inhibiting the abnormal activation of this pathway. Graphical Abstract